2019
DOI: 10.1007/s10546-019-00466-z
|View full text |Cite
|
Sign up to set email alerts
|

Flow Separation in the Lee of a Crater Rim

Abstract: The nearly circular Meteor Crater, Arizona, is located on an extensive, slightly sloping plain, above which a south-westerly katabatic flow forms during undisturbed, clear-sky nights. For the katabatic flow over the upstream crater rim, the resulting flow regime in the lee depends on the upstream wind speed. For a shallow katabatic flow with a wind-speed maximum of about 5 m s −1 or less at a height of about 20 m above the ground, the flow decelerates as it approaches the crater. Cold-air intrusions form, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The Second Meteor Crater Experiment (METCRAX II: Lehner et al ., ) provides a unique dataset of high‐resolution turbulence measurements of persistent relatively deep katabatic flows that can be used to answer some of the questions raised above. Developing over a gentle and extensive mesoscale slope outside Arizona's Meteor Crater, these katabatic flows control the complex flow structure within the crater which was the focus of the METCRAX II campaign (Adler et al ., ; Lehner et al ., ; Whiteman et al ., ; ; Lehner et al ., ). We focus our study on multiple intensive observation periods (IOPs) with well‐developed katabatic flows and a night with synoptically induced flow with the aim of answering the following questions: How does the turbulence structure of relatively deep katabatic flows differ from their more commonly studied shallow katabatic counterparts? What is the dominant length‐scale governing the turbulence structure of these katabatic flows? How does this length‐scale relate to h jet , the surface Obukhov length L and, given the low slope angle, to the SBL height over flat terrain? Is a canonical surface layer with constant fluxes and obeying surface‐layer scaling able to develop in these deeper katabatic flows? …”
Section: Introductionmentioning
confidence: 97%
“…The Second Meteor Crater Experiment (METCRAX II: Lehner et al ., ) provides a unique dataset of high‐resolution turbulence measurements of persistent relatively deep katabatic flows that can be used to answer some of the questions raised above. Developing over a gentle and extensive mesoscale slope outside Arizona's Meteor Crater, these katabatic flows control the complex flow structure within the crater which was the focus of the METCRAX II campaign (Adler et al ., ; Lehner et al ., ; Whiteman et al ., ; ; Lehner et al ., ). We focus our study on multiple intensive observation periods (IOPs) with well‐developed katabatic flows and a night with synoptically induced flow with the aim of answering the following questions: How does the turbulence structure of relatively deep katabatic flows differ from their more commonly studied shallow katabatic counterparts? What is the dominant length‐scale governing the turbulence structure of these katabatic flows? How does this length‐scale relate to h jet , the surface Obukhov length L and, given the low slope angle, to the SBL height over flat terrain? Is a canonical surface layer with constant fluxes and obeying surface‐layer scaling able to develop in these deeper katabatic flows? …”
Section: Introductionmentioning
confidence: 97%
“…Given the elevation of the terraces within the basins, the thinning upward trend in the stratigraphy, and the inconsistent bedding of the layers in the terrace, they could represent an equilibrium elevation in the crater at which erosion outpaces deposition due to the elevated wind speeds, limiting further accumulation within the basins between cycles of deposition (Day & Kocurek, 2016; Kite et al., 2016). In this model, higher elevations within the crater experience increasingly elevated turbulent winds (Greeley et al., 1974; Gundersen et al., 2021; Lehner et al., 2019), which further decrease the net deposition rate for each subsequent layer. Eventually, the accommodation space is exhausted when the net erosion rate is sufficient to prevent the accumulation of additional layers.…”
Section: Discussionmentioning
confidence: 99%
“…For lower wind speeds, could elevated flat areas be a source of large stratification that is advected down the slopes? Advection of stratification is implied in Whiteman et al (2010) and Lehner et al (2016Lehner et al ( , 2019 where a nocturnal boundary layer flows over a plain and then over a crater rim, which then may take several different paths, including flow separation and return flow. The stratification on the plateau might also be large because flat surfaces generally experience greater net radiative cooling than sloped surfaces, given everything else constant (Hoch et al 2011).…”
Section: Stratificationmentioning
confidence: 99%
“…Mahrt (2017) and Pfister et al (2021a, b) examined nocturnal flow over a small-scale plateau that enhanced the turbulence in the lee of the plateau. Organized disturbances, such as those surveyed by Lehner et al (2019), were not identified, possibly because of the failure of the observations to resolve such disturbances or the inability of the microtopography to generate such disturbances. We refer to the enhanced lee turbulence as microscale lee turbulence to distinguish it from larger organized lee disturbances.…”
Section: Introductionmentioning
confidence: 99%